Пегӟон - Станюкович Константин Михайлович (Удмуртское книжное издательство, 1958)
Экземпляры: КР (20020330) / Инвентарный номер: у3474 / Сис.шифр: Р1 / Авт.знак: С 76 / ГРНТИ: 17.82 / ББК: 84(2=411.2)-4